Allergic Interstitial Nephritis Manifesting as a Striated Nephrogram - Irfan Moinuddin; Erika Bracamonte; Bijin Thajudeen; Amy Sussman; Machaiah Madhrira; James Costello (Case Reports in Medicine)
Allergic interstitial nephritis (AIN) is an underdiagnosed cause of acute kidney injury (AKI). Guidelines suggest that AIN should be suspected in a patient who presents with an elevated serum creatinine and a urinalysis that shows white cells, white cell casts, or eosinophiluria. Drug-induced AIN is suspected if AKI is temporally related to the initiation of a new drug. However, patients with bland sediment and normal urinalysis can also have AIN. Currently, a definitive diagnosis of AIN is made by renal biopsy which is invasive and fraught with risks such as bleeding, infection, and hematoma. Additionally, it is frequently unclear when a kidney biopsy should be undertaken. We describe a biopsy proven case of allergic interstitial nephritis which manifested on contrast enhanced Magnetic Resonance Imaging (MRI) as a striated nephrogram. Newer and more stable macrocyclic gadolinium contrast agents have a well-demonstrated safety profile. Additionally, in the presentation of AKI, gadolinium contrast agents are safe to administer in patients who demonstrate good urine output and a downtrending creatinine. We propose that the differential for a striated nephrogram may include AIN. In cases in which the suspicion for AIN is high, this diagnostic consideration may be further characterized by contrast enhanced MRI.